Mezőgazdasági termelőszövetkezetek érdekeltsége természetföldrajzi adottságaik hasznosításában - Perger, Éva (Tér és Társadalom, 1988)
The illusion that organizational and technical modernization would minimalize the impacts of natural factors on agricultural production has been ruled out by the mid-1970s. The results of Hungarian agriculture achieved so far and its role in exports have increased the importance of the reserves still available in the ecological potential of agriculture. The paper calls the attention to the fact that adaptation to natural endowments does not only depend on the use of proper methods for evaluating physical factors or optimal geographical distribution of agricultural production but first of all on how much production units (state- and co-operative farms and individual farmers) are interested in thís. In the first part of the paper the author draws a conceptual outline based on available economic and sociological publications, of the impacts of socio-economic environment, influenced by the economic mechanism and the local system of interests, on the attitude of agricultural co-operatives to natural endowments. The second part summarizes the findings of two case studies made in two co-operatives with very different nautral endowments. The last part contains the author's conclusions drawn from a comparison between the results of the conceptual analysis and the empirical findings.